Anything but the Law Essays on Politics & Economics - Thomas Tommy (SIRD, 2016)
"With legal acumen and moral vision, Tommy Thomas presents a compelling narrative for a version of statehood that is inclusive and accountable…Thomas offers a riveting chronicle and judicious analysis of two contentious political issues - the bifurcation of Islamic state vs secularism and the social contract…The author laments that his foray into economics is with much trepidation; but he seems to be an advertent economist in his essays on unbridled US market capitalism and financial crisis. This might turn him into a 'public enemy' of the 'robber barons'" - Anwar Ibrahim, Former Deputy Prime Minister & Former Leader of the Opposition.